Diversity strategies focused on employees with a migration background: An empirical investigation based on resource dependence theory - Renate Ortlieb; Barbara Sieben (Management Revue, 2008)
In our paper, we develop a typology of diversity strategies through combining elements of strategy research, diversity research, and resource dependence theory. We focus on the question why people with a migration background are (not) employed by organizations. We argue that employment decisions are based on the evaluation of critical resources and the quest to secure their accrual. We identify six diversity strategies, designate each by the importance of respective resources, and derive propositions regarding their relation to competitive strategies. We confront these propositions with empirical data stemming from 500 companies. Correspondence analyses reveal various relationships between diversity and competitive strategies and moderating effects of the company size and the industrial sector. In addition, the robustness of our typology is demonstrated.
Keywords: 650; diversity; migration background; employment strategies; resource dependence theory; correspondence analysis